TANTANGAN “POLYGAMOUS STORE” : STUDI EMPIRIS PENGUATAN ATRIBUT TOKO DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN PADA GERAI ALFAMART DI KOTA SEMARANG - Andi Setiawan (Universitas Islam Nahdlatul Ulama Jepara, 2018)
Purpose – This study aims to investigate how the influences of store attributes on store loyalty can be mediated by the store satisfaction framework.Design/methodology/approach – The survey data were collected from selected retail stores respondent using accidental sampling. The hypotheses were tested using structural equation modeling. This research model uses 5 variables and 25 indicators that form a store loyalty model. in this research model has been developed and 6 hypotheses have been formulated to answer the problem of this research. Data or a questionnaire distributed to The number of questionnaires distributed by 250 questionnaires in the Semarang region. The results of the selection of incoming questionnaires from 250 questionnaires, only 180 questionnaires were stated complete, so that it was feasible to be analyzed at a later stage. Because this study uses questionnaire data as primary data, so it takes steps to test the question (questionnaire) to find out whether the question is valid or not Findings - The findings of this study help practitioners by empirically demonstrating that combined store satisfaction from consumers with store and affective loyalty programs mediate the influence of attributes such as the store atmosphere, store location, store personnel and so on the quality of the relationship between the shop and the customer. Therefore, store satisfaction alone cannot create strong loyalty and customer relationships. Conversely the existence of store attributes such as atmosphere, location, personnel will not perfectly shape store loyalty if it is not mediated by cognitive satisfactionResearch limitations / implications - Limited research on Alfamart customers, has not expanded the test of users of online purchasing facilities that use Alfamart's online facilities with Alfamind, so that the results can be more enriching, reinforcing past theories and research. In addition, this research draws on the requirements of respondents having a member card (Ponta) Alfamart as well as having a card from a competitor's retail. The results of testing this hypothesis cannot prove the effect of store location on store loyalty in order to get results that match expectations.Practical implications - The findings suggest that, in order to increase of store loyalty. The model output in this study can provide a positive contribution to PT. Sumber Alfaria Trijaya, Tbk. in an effort to realize store loyalty in the form of suggestions for managerial implications. Managerial advice is intended for PT. Sumber Alfaria Trijaya, Tbk. in formulating store location management policies in the future.Originality / value - This research adds value to the domain of store loyalty research by empirically establishing the mediating role played by the cognitive satisfaction-affective store attributes such as atmosphere, location, personnel framework in shaping the influences of loyalty programs designed by store management on the final store loyalty and customer–store relationship.